Carpenter bees (Apidae: Xylocopini: Xylocopa) from Maranhão, Northeast Brazil - Ferreira, Luciano André Chaves; Giannini, Tereza Cristina; Albuquerque, Patrícia Maia Correia De; Zanella, Fernando César Vieira (Zootaxa, 2024)
We present a list of Xylocopa Latreille species that occur in Maranhão State, a region where several physiognomic formations characteristic of the Amazon, Cerrado, and Caatinga biomes overlap. The information was compiled through numerous surveys conducted in this territory, in addition to direct consultation in scientific collections, which have many unpublished records. Twelve species belonging to three subgenera were documented: Xylocopa (Neoxylocopa) amazonica Enderlein, 1913, X. (N.) aurulenta (Fabricius, 1804), X. (N.) cearensis Ducke, 1910, X. (N.) frontalis (Olivier, 1789), X. (N.) grisescens Lepeletier, 1841, X. (N.) hirsutissima Maidl, 1912, X. (N.) nigrocincta Smith, 1854, X. (N.) transitoria Pérez, 1901, X. (Schonnherria) macrops Lepeletier, 1841, X. (S.) muscaria (Fabricius, 1775), X. (S.) subcyanea Pérez, 1901 and X. (Stenoxylocopa) sp. Of these, two species are reported as first records for Maranhão (X. hirsutissima and X. subcyanea), one for Brazil (X. transitoria), and one for science (X. (Stenoxylocopa) sp.—not yet published).